Research is needed to inform environmental management of hydrothermally inactive and extinct polymetallic sulfide (PMS) deposits. (November 2020) - Van Dover, C.L.; Colaço, A.; Collins, P.C.; Croot, P.; Metaxas, A.; Murton, B.J.; Swaddling, A.; Boschen-Rose, R.E.; Carlsson, J.; Cuyvers, L.; Fukushima, T.; Gartman, A.; et al.
Abstract: Polymetallic sulfide (PMS) deposits produced at hydrothermal vents in the deep sea are of potential interest to miners. Hydrothermally active sulfide ecosystems are valued for the extraordinary chemosynthetic communities that they support. Many countries, including Canada, Portugal, and the United States, protect vent ecosystems in their Exclusive Economic Zones. When hydrothermal activity ceases temporarily (dormancy) or permanently (extinction), the habitat and associated ecosystem change dramatically. Until recently, so-called "inactive sulfide" habitats, either dormant or extinct, received little attention from biologists. However, the need for environmental management of deep-sea mining places new imperatives for building scientific understanding of the structure and function of inactive PMS deposits. This paper calls for actions of the scientific community and the emergent seabed mining industry to i) undertake fundamental ecological descriptions and study of ecosystem functions and services associated with hydrothermally inactive PMS deposits, ii) evaluate potential environmental risks to ecosystems of inactive PMS deposits through research, and iii) identify environmental management needs that may enable mining of inactive PMS deposits. Mining of some extinct PMS deposits may have reduced environmental risk compared to other seabed mining activities, but this must be validated through scientific research on a case-by-case basis. Highlights: Metal-rich polymetallic sulfide deposits (PMS) are of interest to deep-sea miners. The biota and ecology of hydrothermally inactive and extinct PMS deposits are mostly unknown. Scientific research is needed to inform environmental management of mining of PMS deposits.